Racial Necrogeographies and the Making of White Space: The Life and Death of Nineteenth-Century Indigenous and Black Burial Places in Rural Ontario - Felepchuk, William (American Indian Culture and Research Journal, 2019)
In this article, I unearth the dehumanizing racial violence of the destruction of Saugeen Anishinaabe and Black community burial places in Grey County, Ontario by settler whites. I trace how the fate of particular sites might represent a wider pattern of necrogeographical violence on the part of whites. I also explore the importance of such sites to Indigenous and Black communities, their reclamation by communities, and white backlash to such actions. In Grey County, the making of a white landscape has gone hand in hand with the destruction of the hallowed places of Indigenous and Black communities.